The Effect of Cromolyn Sodium and Nedocromil Sodium Administered by A pressurized Aerosol with A spacer Device on Exercise-Induced Asthma in Children - F. M. de Benedictis; G. Tuteri; A. Niccoli; D. Mezzetti; L. Rossi; L. Bruni (Hindawi Limited, 1994)
To compare the effectiveness of cromolyn sodium (CS) (10 mg) and nedocromil sodium (NS) (4 mg) administered by a metered dose inhaler (MDI) with a spacer device in preventing exercise-induced asthma (EIA), eight asthmatic children with EIA were studied in a randomized double-blind, cross-over, placebo-controlled study, CS and NS provided significant, comparable protection from EIA and both were better than placebo. We conclude that CS and NS administered by a pressurized aerosol with a spacer device provide equal protection against EIA in children.